VD_FINDINFO Arrêt / 2014 / 722 vom 25. September 2014 - VD Tribunal cantonal (2014)
RENTE D'INVALIDITÉ, AIASSURANCE, RENTE ÉCHELONNÉE, REVENU SANS INVALIDITÉ | 28 LAI, 4 LAI, 16 LPGA, 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA